Redesigning the Principle of Justice in Labor Disputes - Arpangi, Arpangi; Sanni , Tajudeen (Lembaga Contrarius Indonesia, 2025)
Disputes between workers and employers are inevitable in industrial relations, requiring an effective and fair dispute resolution mechanism. Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes currently serves as the primary legal basis for resolving such disputes in Indonesia. However, this law, particularly Article 83 paragraphs (1) and (2), has drawn significant criticism for failing to reflect the values of justice, procedural efficiency, and legal certainty. This study aims to examine and analyze the weaknesses of the existing regulation on filing labor dispute lawsuits at the Industrial Relations Court and to reconstruct these provisions based on the principles of justice. This research employs the theory of Pancasila justice, legal system theory, and progressive legal theory, with a constructivist paradigm and a legal research approach. The study uses descriptive-analytical specifications, collecting primary data from field studies and secondary data from literature and legal materials. The data analysis uses qualitative methods. The research findings identify three main issues: First, the regulation lacks justice values and places an administrative burden on judges, causing procedural inefficiencies. Second, weaknesses exist in the legal structure, substance, and culture, particularly regarding ineffective bipartite and tripartite dispute resolution and limited worker access to justice. Third, the study proposes reconstructing Article 83 by delegating administrative verification duties to the clerk’s office, ensuring procedural efficiency and strengthening the realization of justice in industrial relations dispute resolution.